Distribution Channel Patterns and The Actors Welfare of Marine Fishery Supply Chain in Arjasa, Kangayan and Sapeken in Kangean Islands - Indahsari, Kurniyati; Farid, Akhmad (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
The actors’ welfare of marine fishery supply chain in the three sub-districts in Kangean Islands, namely Sapeken, Arjasa and Kangayan, are different even though they access to the same marine fisheries resources. The marine fisheries in Sapeken are more prosperous than those in Arjasa and Kangayan. This study aimed at identifying the distribution channel patterns of marine fishery products supply chain in Kangean Islands which providing an explanation of the actors’ welfare differences. In-depth interviews with various actors were conducted to formulate the distribution channel patterns of marine fishery products. Quantitative survey data of 102 respondents from marine fisheries were processed descriptively to determine the actors’ welfare. Research showed that the distribution channel patterns in Arjasa and Kangayan vary but are limited in the local market and the islands communities as the final consumers. It causes the low products prices. Meanwhile, the distribution pattern in the Sapeken is able to penetrate markets outside the Kangean Islands with high product prices. Therefore, it is not surprising if the actors’ welfare in Arjasa and Kangayan sub districts are lower than the actors’ welfare in Sapeken.